GAGAL JANTUNG - Mariyono, Harbanu H; Santoso, Anwar (journal of internal medicine, 2008)
Heart failure were the end stage of all heart disease and the cause of the increasing morbidity andmortality among patient. Almost five percent from all inhospital patient were heart failure. Heart failure hasbeen defined as the failure of the heart to pump blood to systemic. It can be classify into acute, acutedecompensated and chronic heart failure. New York Heart Association, Stevenson, Forrester have madeclassification based on the clinical symptoms. All cardiac problems can ended into heart failure, thepathogenesis was very complex including renin-angiotensin-aldosteron system, neurohormonal, sympatic nervesystem, nattriuretic peptide, and others. Twelve leads ECGs, echocardiography, chest x-rays, blood chemistries,catheterisation can help us diagnose patient with heart failure. Management of heart failure consist ofmanagement of acute and chronic heart failure, non drugs management, drugs and even an invasive treament.